Relation between Mechanical Properties and Microstructure of Cast Aluminum Alloy AlSi9Cu3 - Panuskova, M.; Tillova, E.; Chalupova, M. (Проблемы прочности, 2008)
One common material for engine applications is the AlSi9Cu3 alloy. This alloy has a good castability, excellent machinability, medium strength, and low specific weight. The study was focused on the investigation of the effect of the solution heat treatment on the microstructure and mechanical properties of the alloy (strength - Rm, hardness - HBS). The temperatures of the solution heat treatment were 505°C, 515°C, and 525°C± 5°C and the solution time rangedfrom 0 to 32 h (0, 2, 4, 8, 16, and 32 h). Alloy AlSi9Cu3 contained α-matrix, eutectic silicon, and other Fe- and Cu-rich phases with different morphology (needle-like, Chinese script, skeleton-like, blocky, etc.). The results obtained revealed the relation between the mechanical properties and the morphologies ofthe eutectic silicon and thepredominant copper-rich phase Al-Al2Cu-Si during the solution treatment. Сплав AlSi9Cu3 является одним из материалов, широко используемых в двигателестроении. Он имеет хорошую жидко-текучесть, отличную обрабатываемость, среднюю прочность и низкий удельный вес. Основное внимание в данном исследовании было направлено на исследование влияния гомогенизации на микроструктуру и механические свойства этого сплава (прочность исходного материала Кт, твердость НВХ). Обработка проводилась при температурах 505, 515 и 525°С± 5°С, длительность обработки колебалась в пределах 0...32 ч (0, 2, 4, 8, 16 и 32 ч). Сплав AlSi9Cu3 содержал α-матрицу, эвтектический кремний и другие фазы, богатые железом и медью, имеющие различную структуру (игольчатую, иероглифоподобную, ажурную, глыбообразную и т.п.). Полученные результаты показали существование зависимости между механическими свойствами и морфологиями эвтектического кремния и богатой медью Al-Al2Cu-Si-фазы, преобладающей во время гомогенизации.